Pescado Enterprise : Automatic Fish Scale Remover / Fareez Azeem Badrulhisam ...[et al.] - Badrulhisam, Fareez Azeem; Khairul Fauzi, Amirul Hakimi; Zulkapri, Ladyn; Mohamad Nor Azmi, Mohamad Farhan; Naharudin, Muhamad Amir Hazman (2016)
One of our company's key performance indicator (KPI) is to ensure that customer satisfaction is the highest quality possible. Another KPI is the assurance of the safety of our customers when they use our company's product. These two KPl's are the main focus of our company and will continue to be so until another area that a KPI is needed. Our company's policy is always to put the customers' needs above everything which will cover the two KPl's mentioned earlier, customer satisfaction and also their safety.